A kind of glue containing polycarbonate and preparation method thereof

By optimizing the glue formula, the thermal conductivity and shear strength of the glue containing polycarbonate is improved, and the problem of poor heat dissipation performance of existing glues during fast charging is solved, and the performance needs of the battery pack under high fast charging conditions is met.

CN119161842BActive Publication Date: 2025-03-07SHANDONG ZHONGKE YUYE NEW ENERGY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411660301.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-07
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing polycarbonate-containing glue has poor thermal conductivity and average shear strength, which cannot meet the heat dissipation needs of new energy vehicle battery packs during fast charging, affecting the performance of the battery pack.

Method used

By optimizing the formula of the glue, the mass ratio is adjusted to improve the thermal conductivity and shear strength of the glue.

Benefits of technology

It achieves high thermal conductivity and high shear strength of the glue, which is suitable for efficient heat dissipation of the battery pack, and improves the performance of the battery pack during fast charging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a polycarbonate-containing glue and a preparation method thereof, and belongs to the technical field of glue. 26 parts of polycaprolactone triol, 0.4-0.5 parts of benzoyl peroxide, 1-3 parts of hydroquinone-bis(β-hydroxyethyl) ether, 25 parts of polycarbonate diol, 45-48 parts of hexagonal boron nitride, 4 parts of γ-methacryloxypropyltrimethoxysilane and 35-38 parts of isocyanate. The mass ratio of hexagonal boron nitride, γ-methacryloxypropyltrimethoxysilane and isocyanate is 45-46:4:36. The present invention improves thermal conductivity and also has good shear strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glue, and more specifically, relates to a glue containing polycarbonate and a preparation method thereof. Background Art

[0002] At present, new energy vehicles have higher and higher requirements for the fast charging performance of battery packs. Glue is often poured on the outside of the battery, and glue is needed to fix the battery to the battery pack box. Since the battery generates heat while charging, the glue can effectively transfer the heat to the box, making the heat of the battery controllable, so that it can adapt to fast charging and improve the charging efficiency of the battery pack.

[0003] At present, polycarbonate-containing glue contains acrylic substances, such as hydroxyethyl dimethacrylate of phthalic anhydride. The addition of such substances will affect the thermal conductivity of the glue, thereby affecting the heat transfer of the battery pack, making the heat dissipation of the battery pack limited during fast charging, limiting the heat dissipation performance of the battery pack. At the same time, if you only pursue thermal conductivity and increase the glue content, the energy density of the battery pack will be affected. At the same time, if you reduce the glue content and blindly pursue low content, the shear strength of the glue is also crucial, which affects the mechanical strength of the entire battery pack, and the mechanical strength of the battery pack cannot be guaranteed.

[0004] Therefore, it is necessary to prepare a glue with high thermal conductivity and high shear strength. Summary of the invention

[0005] In view of the problem that the polycarbonate-containing glue in the prior art has poor thermal conductivity, general shear strength, and cannot make the battery pack have good fast charging performance, that is, the fast charging heat dissipation is poor, which further leads to the degradation of battery pack performance, the present invention provides a polycarbonate-containing glue and a preparation method thereof.

[0006] In order to solve the above problems, the technical solution adopted by the present invention is as follows: A polycarbonate-containing glue of the present invention is composed of the following raw materials in parts by weight:

[0007] 26 parts of polycaprolactone triol, 0.4-0.5 parts of benzoyl peroxide, 1-3 parts of hydroquinone-bis(β-hydroxyethyl) ether, 25 parts of polycarbonate diol, 45-48 parts of hexagonal boron nitride, 4 parts of γ-methacryloxypropyltrimethoxysilane and 35-38 parts of isocyanate.

[0008] In some specific embodiments, the glue is used for thermal conductivity of batteries and battery packs.

[0009] In some specific embodiments, the mass ratio of hexagonal boron nitride, γ-methacryloxypropyltrimethoxysilane and isocyanate is 45-46:4:36. When the mass ratio of hexagonal boron nitride, γ-methacryloxypropyltrimethoxysilane and isocyanate is optimized to 45-46:4:36, compared with the mass ratio of hexagonal boron nitride, γ-methacryloxypropyltrimethoxysilane and isocyanate of 47:4:36, its shear strength and thermal conductivity are higher, which better matches the requirements of faster charging battery packs. The possible reason is that there is too much hexagonal boron nitride, which has limited effect on thermal conductivity when hexagonal boron nitride, γ-methacryloxypropyltrimethoxysilane and isocyanate are mixed, but too much hexagonal boron nitride affects the synergistic effect of hexagonal boron nitride, γ-methacryloxypropyltrimethoxysilane and isocyanate, resulting in a decrease in shear strength.

[0010] In some specific embodiments, the mass ratio of hexagonal boron nitride, γ-methacryloxypropyltrimethoxysilane and isocyanate is 46:4:36.

[0011] In some specific embodiments, the γ-methacryloxypropyltrimethoxysilane is γ-methacryloxypropyltrimethoxysilane KH-570.

[0012] The present invention also protects a method for preparing a polycarbonate-containing adhesive, which is used for preparing any of the above-mentioned polycarbonate-containing adhesives. According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 100r / min, and 35-38 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 45-48 parts of hexagonal boron nitride were added and the mixture was stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to be -0.2MPa and maintained for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4-0.5 parts of benzoyl peroxide and 1-3 parts of hydroquinone-bis(β-hydroxyethyl) ether were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue. By controlling the stirring time at a higher speed of 100 r / min and selecting a suitable temperature, from 80°C in Comparative Example 10 to 106°C in Example 1, the isocyanate can be fully mixed and the hexagonal boron nitride can have better contact, and then γ-methacryloxypropyltrimethoxysilane is added to improve its shear strength and thermal conductivity. Beneficial Effects

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] (1) The method for preparing a polycarbonate-containing glue of the present invention improves the thermal conductivity and shear strength of the glue by optimizing the reaction conditions and the order of adding the components and the addition of the components, and is suitable for heat dissipation of battery packs.

[0015] (2) The adhesive of the present invention optimizes the formula, especially the suitable mass range of hexagonal boron nitride, γ-methacryloxypropyltrimethoxysilane and isocyanate, does not use acrylic substances, and the three substances act synergistically. The silane of trimethoxysilane and isocyanate substances, -CN and hexagonal boron nitride are in contact with each other, exerting thermal conductivity and maintaining shear strength, thereby having high thermal conductivity and shear strength. DETAILED DESCRIPTION

[0016] The more detailed description of the embodiments of the present invention below is not intended to limit the scope of the claimed invention, but is merely for illustration and not to limit the description of the features and characteristics of the present invention, so as to propose the best mode for performing the present invention, and to be sufficient to enable those skilled in the art to implement the present invention. However, it should be understood that various modifications and variations may be made without departing from the scope of the present invention as defined by the appended claims. The detailed description should be considered only as illustrative, not restrictive, and if there are any such modifications and variations, they will all fall within the scope of the present invention described herein. In addition, the background technology is intended to illustrate the current status and significance of the research and development of the present technology, and is not intended to limit the present invention or the application field of the present application and the present invention.

[0017] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs; the terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0018] The present invention is further described below in conjunction with specific embodiments. Example 1

[0019] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 100r / min, and 36 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 45 parts of thermal conductive filler hexagonal boron nitride were added and the mixture was stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to -0.2MPa for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4 parts of catalyst benzoyl peroxide and 1 part of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue.

[0020] In the present application, the isocyanate is diphenylmethane diisocyanate. Example 2

[0021] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 100r / min, and then 36 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 46 parts of thermal conductive filler hexagonal boron nitride were added and the mixture was stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to be -0.2MPa and maintained for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4 parts of catalyst benzoyl peroxide and 1 part of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue. Example 3

[0022] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 100r / min, and 36 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 47 parts of thermal conductive filler hexagonal boron nitride were added and the mixture was stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to -0.2MPa for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4 parts of catalyst benzoyl peroxide and 1 part of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue. Example 4

[0023] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 100r / min, and 36 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 48 parts of thermal conductive filler hexagonal boron nitride were added and the mixture was stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to be -0.2MPa and maintained for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4 parts of catalyst benzoyl peroxide and 1 part of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue. Example 5

[0024] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 100r / min, and 36 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 45 parts of thermal conductive filler hexagonal boron nitride were added and the mixture was stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to be -0.2MPa and maintained for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.5 parts of catalyst benzoyl peroxide and 1 part of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue. Example 6

[0025] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 100r / min, and 36 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 45 parts of thermal conductive filler hexagonal boron nitride were added and the mixture was stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to -0.2MPa for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4 parts of catalyst benzoyl peroxide and 2 parts of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue. Example 7

[0026] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 100r / min, and 36 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 45 parts of thermal conductive filler hexagonal boron nitride were added and the mixture was stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to be -0.2MPa and maintained for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4 parts of catalyst benzoyl peroxide and 3 parts of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue. Example 8

[0027] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 100r / min, and 38 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 45 parts of thermal conductive filler hexagonal boron nitride were added and the mixture was stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to be -0.2MPa and maintained for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4 parts of catalyst benzoyl peroxide and 1 part of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue.

[0028] Comparative Example 1

[0029] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 100r / min, and 36 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 45 parts of thermal conductive filler hexagonal boron nitride were added and the mixture was stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to be -0.2MPa and maintained for 30min. The mixture was then cooled to 70°C. 4 parts of hydroxyethyl dimethacrylate of isophthalic anhydride and 0.4 parts of catalyst benzoyl peroxide and 1 part of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue.

[0030] Comparative Example 2

[0031] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 100r / min, and then 30 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 45 parts of thermal conductive filler hexagonal boron nitride were added and the mixture was stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to be -0.2MPa and maintained for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4 parts of catalyst benzoyl peroxide and 1 part of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue.

[0032] Comparative Example 3

[0033] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 100r / min, and then 40 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 45 parts of thermal conductive filler hexagonal boron nitride were added and the mixture was stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to -0.2MPa for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4 parts of catalyst benzoyl peroxide and 1 part of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue.

[0034] Comparative Example 4

[0035] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 100r / min, and then 36 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 40 parts of thermal conductive filler hexagonal boron nitride were added and the mixture was stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to be -0.2MPa and maintained for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4 parts of catalyst benzoyl peroxide and 1 part of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue.

[0036] Comparative Example 5

[0037] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 100r / min, and 36 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 50 parts of hexagonal boron nitride, a thermal conductive filler, were added and stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to -0.2MPa for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4 parts of catalyst benzoyl peroxide and 1 part of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was continued to be stirred for 2h to obtain a polycarbonate-containing glue.

[0038] Comparative Example 6

[0039] The difference from Example 1 is that the thermal conductive filler (hexagonal boron nitride) is 45 parts, γ-methacryloxypropyltrimethoxysilane is 4 parts, and isocyanate (diphenylmethane diisocyanate) is 30 parts. The rest is the same as Example 1.

[0040] Comparative Example 7

[0041] The difference from Example 1 is that the thermal conductive filler (hexagonal boron nitride) is 45 parts, γ-methacryloxypropyltrimethoxysilane is 3 parts, and isocyanate (diphenylmethane diisocyanate) is 35 parts. The rest is the same as Example 1.

[0042] Comparative Example 8

[0043] The difference from Example 1 is that the thermal conductive filler (hexagonal boron nitride) is 40 parts, γ-methacryloxypropyltrimethoxysilane is 4 parts, and isocyanate (diphenylmethane diisocyanate) is 35 parts. The other parts are the same as Example 1.

[0044] Comparative Example 9

[0045] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 106°C / 2h at a speed of 70r / min, and 36 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 70r / min for 2h and the temperature was maintained at 70°C. Then 45 parts of thermal conductive filler hexagonal boron nitride were added and the mixture was stirred at a speed of 70r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 106°C at a speed of 100r / min. The vacuum environment was controlled to be -0.2MPa and maintained for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4 parts of catalyst benzoyl peroxide and 1 part of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue.

[0046] Comparative Example 10

[0047] According to the mass components, 25 parts of polycarbonate diol were weighed and put into a reactor. The temperature was raised to 80°C / 2h at a speed of 100r / min, and 36 parts of isocyanate were added and mixed evenly. The mixture was stirred at a speed of 100r / min for 2h and the temperature was maintained at 70°C. Then 45 parts of thermal conductive filler hexagonal boron nitride were added and the mixture was stirred at a speed of 100r / min for 2h. Then 26 parts of polycaprolactone triol were weighed and put into a reactor. The temperature was maintained at 80°C at a speed of 100r / min. The vacuum environment was controlled to -0.2MPa for 30min. The mixture was then cooled to 70°C. 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4 parts of catalyst benzoyl peroxide and 1 part of chain extender (hydroquinone-bis(β-hydroxyethyl) ether) were added and the reaction was stirred for 2h to obtain a polycarbonate-containing glue.

[0048] test:

[0049] Shear strength test: used to adhere aluminum to aluminum (2mm), obtain test specimens, and test shear strength according to GB / T 7124-2008; thermal conductivity test: using steady-state heat flow method, test according to ASTM D5470. The test results are recorded in Table 1.

[0050] Table 1. Comparison of properties of adhesives obtained in various implementation methods

[0051]

[0052] By comparing Example 1 and Comparative Example 1, we found that only by adding γ-methacryloxypropyltrimethoxysilane can a synergistic effect be exerted with isocyanate and thermally conductive filler. The thermal conductivity and shear strength of Example 1 are both higher, and the increase ratio of the thermal conductivity of Example 1 is higher. Since no acrylic substances are added, silane substances can cooperate with groups such as -CN, thereby improving the thermal conductivity (greater improvement) and shear strength.

[0053] Comparative Example 2-Comparative Example 3 By changing the isocyanate (diphenylmethane diisocyanate) to 30 parts and the isocyanate (diphenylmethane diisocyanate) to 40 parts, we found that the shear strength and thermal conductivity were both reduced compared with Example 1.

[0054] When 40 parts of thermal conductive filler (hexagonal boron nitride) and 50 parts of thermal conductive filler (hexagonal boron nitride) were added to Comparative Example 4-Comparative Example 5, we found that their shear strength and thermal conductivity were somewhat decreased compared with Example 1.

[0055] By comparing Example 1 with Comparative Examples 6-8, when the thermal conductive filler is 45-48 parts, γ-methacryloxypropyltrimethoxysilane is 4 parts and isocyanate is 35-38 parts, hexagonal boron nitride, γ-methacryloxypropyltrimethoxysilane and isocyanate work synergistically to improve its shear strength and thermal conductivity, and have a better effect in this range.

[0056] By comparing Examples 1-4, we found that when the mass ratio of the optimized thermally conductive filler (hexagonal boron nitride), γ-methacryloxypropyl trimethoxy silane and isocyanate is 45-46:4:36, compared with the mass ratio of the thermally conductive filler, γ-methacryloxypropyl trimethoxy silane and isocyanate being 47:4:36 and 48:4:36, the shear strength and thermal conductivity are higher, which better matches the high-fast charging battery pack requirements. The possible reason is that there are too many thermally conductive fillers, so that when the thermally conductive filler, γ-methacryloxypropyl trimethoxy silane and isocyanate are mixed, the thermal conductivity has a limited effect, but too much thermally conductive filler affects the synergistic effect of the thermally conductive filler, γ-methacryloxypropyl trimethoxy silane and isocyanate, resulting in a decrease in shear strength. Comparing Example 1 and Example 5, the shear strength is better when benzoyl peroxide is set to 0.4 parts.

[0057] Comparative Example 1, Example 6-Example 7 show that the shear strength and thermal conductivity can be improved when the hydroquinone-bis(β-hydroxyethyl) ether is 1-3 parts, but the shear strength performance is better when the chain extender (hydroquinone-bis(β-hydroxyethyl) ether) is 1 part. Comparative Example 1 and Example 8 show that the shear strength and thermal conductivity can be improved when the isocyanate is 35-38 parts, but the shear strength performance is better when the isocyanate is 35 parts.

[0058] By comparing Comparative Examples 9-10 with Example 1, we found that by controlling the stirring time at a higher speed of 100 r / min and selecting a suitable temperature, from 80°C in Comparative Example 10 to 106°C in Example 1, the isocyanate can be fully mixed and the thermally conductive filler hexagonal boron nitride can have better contact, and then combined with γ-methacryloxypropyltrimethoxysilane, its shear strength and thermal conductivity can be improved.

[0059] The present invention has been described in detail above in conjunction with specific exemplary embodiments. However, it should be understood that various modifications and variations may be made without departing from the scope of the present invention as defined by the appended claims. The detailed description should be considered only as illustrative, not restrictive, and any such modifications and variations, if any, will fall within the scope of the present invention described herein. In addition, the background art is intended to illustrate the current status and significance of the research and development of the present technology and is not intended to limit the present invention or the application field of the present application and the present invention.

[0060] More specifically, although exemplary embodiments of the present invention have been described herein, the present invention is not limited to these embodiments, but includes any and all embodiments that are recognizable by those skilled in the art based on the foregoing detailed description, such as combinations between the various embodiments, adaptive changes and / or replacements. The limitations in the claims may be interpreted broadly based on the language used in the claims and are not limited to the examples described in the foregoing detailed description or during the implementation of the application, which examples should be considered non-exclusive. Any steps listed in any method or process claim may be performed in any order and are not limited to the order presented in the claim. Therefore, the scope of the present invention should be determined solely by the attached claims and their legal equivalents, rather than by the description and examples given above.

[0061] Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definitions in this specification shall prevail. When flow, power, refractive index, time, or other values ​​or parameters are expressed as ranges, preferred ranges, or a series of upper preferred values ​​and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 is understood to include any number, combination of numbers, or subrange selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, and all decimal values ​​between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested sub-ranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction.

Claims

1. A polycarbonate-containing glue, characterized in that: The invention is composed of the following raw materials in parts by mass: 26 parts of polycaprolactone triol, 0.4-0.5 parts of benzoyl peroxide, 1-3 parts of hydroquinone-bis(β-hydroxyethyl) ether, 25 parts of polycarbonate diol, 45-48 parts of hexagonal boron nitride, 4 parts of γ-methacryloxypropyltrimethoxysilane and 35-38 parts of isocyanate; The preparation method of polycarbonate-containing glue comprises the following steps: according to the mass components, 25 parts of polycarbonate diol are weighed, put into a reactor, and the temperature is raised to 106°C / 2h at a speed of 100r / min, and then 35-38 parts of isocyanate are added and mixed evenly, and the mixture is stirred at a speed of 100r / min for 2h, and the temperature is maintained at 70°C, and then 45-48 parts of hexagonal boron nitride are added, and the mixture is continuously stirred at a speed of 100r / min for 2h, and then 26 parts of polycaprolactone triol are weighed and put into a reactor, and the temperature is maintained at 106°C at a speed of 100r / min, and the vacuum environment is controlled to be -0.2MPa and maintained for 30min, and then the temperature is lowered to 70°C, and 4 parts of γ-methacryloxypropyltrimethoxysilane, 0.4-0.5 parts of benzoyl peroxide, and 1-3 parts of hydroquinone-bis(β-hydroxyethyl) ether are added, and the mixture is continuously stirred and reacted for 2h to obtain the polycarbonate-containing glue.

2. The polycarbonate-containing adhesive according to claim 1, characterized in that: The mass ratio of the hexagonal boron nitride, γ-methacryloxypropyltrimethoxysilane and isocyanate is 45-46:4:

36.

3. The polycarbonate-containing adhesive according to claim 1, characterized in that: The mass ratio of the hexagonal boron nitride, γ-methacryloxypropyltrimethoxysilane and isocyanate is 46:4:36.

Citation Information

Patent Citations

  • Preparation method of high thermal conductivity insulative hexagonal boron nitride / polycarbonate composite material

    CN106189165A

  • Heat-conducting structural adhesive and preparation method thereof

    CN110938404A